Cross-Genre Stylistic Construction of Motherhood in Mustofa Bisri’s Ibu and Rhoma Irama’s Keramat - Mualim, Fahrudin; Gridi, Mehdi; Safarova, Mehriban (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to examine the comparative use of figurative language in Mustofa Bisri’s poem Ibu and Rhoma Irama’s song lyric Keramat, identify their expressive and persuasive functions, and formulate pedagogical implications for Indonesian language and literature learning. Methodology: This research employed a qualitative descriptive design with a comparative stylistic approach. Data were collected through documentation and close reading techniques from the poem Ibu and the song lyric Keramat. Data were classified using a figurative language identification table and analyzed through qualitative content analysis and functional stylistic interpretation. Main Findings: The findings reveal that both texts sacralize motherhood through similar lexical fields but differ in stylistic orientation and communicative function. The poem predominantly employs metaphor and symbolism to construct spiritual elevation and reflective admiration, while the song lyric utilizes hyperbole, repetition, irony, and imperative structures to deliver moral persuasion and social criticism. Novelty/Originality of this study: This study offers a cross-genre comparative stylistic model integrating structural analysis, functional interpretation, and pedagogical implications. Unlike previous studies that examine poetry and song lyrics separately, this research demonstrates how genre differences influence figurative language functions and provides an integrative framework for Indonesian literary education.